#TITLE_ALTERNATIVE# - HASNA RUFAIDA (NIM 12903004), NIDA
This thesis presents an analysis of tides in the stations in Padang, Bangka, Pari, Benoa, and Kupang which have thirty days range of data, using World Tides and TAN programmes and, admiralty method. Then, the results are analysed and compare. The World Tides and TAN programmes basically using Least Square method, which is a harmonic analysis method to gain solution of the tides elevation equation. World Tides based on Matlab, using Graphical User Interface (GUI), while TAN uses .tif as its input which we can manually decide the number of tides component. Admiralty method used only for short-range data (1, 7, 15, and 29 days) with relatively few results, only nine main tides components, that is, M2, S2, K2, N2, O1, K1, P1, MS4, and M4. World Tides and TAN programmes, and admiralty method have their own plus and minus. World Tides is a public domain programme, have the ability to analyse ≥ 15 days data using seven tides components (O1, K1, N2, M2, S2, M4, and MS4) and synodic period based components, and we can make prediction at the same time. However, World Tides can not be use to analyse hollow data, can not be modified, inaccurate prediction and can not be use for short range data (< 15 days). TAN programme, on the other hand, can be modified, can be use to analyse hollow data and ≥ 30 days data. Nevertheless, it is not public domain, can not be use for short range data (≤ 15 days), and we have to make prediction separately. While admiralty method is very user friendly and can be use to analyse short-range data; but it takes more detail tabulation, can not be used for long-range data (> 29 days), only produces nine tides components, can not analyse hollow data. Although each of them has their own excesses and flaws, we can tell which programme or method that is accurate by observing the smallest error. For fifteen days data, the error of World Tides is smaller than of admiralty method, while for thirty days the smallest error showed by TAN. Between the five observed locations, Pari has the smallest error. It results from its semi-closed condition. On the other hand, the biggest error is in Kupang, because it is near Hindia Ocean so the non-astronomic factors are strong.